Pengaruh Temuan Audit Dan Tindak Lanjut Rekomendasi Hasil Pemeriksaan Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Pada Kabupaten Dan Kota Provinsi Jawa Barat Tahun 2019-2023) - Zahwah Aqilah Junaedi; Arie Apriadi Nugraha (Indonesian Accounting Research Journal, 2025)
The quality of local government financial reports reflects the extent to which financial information is presented in accordance with applicable accounting standards. The preparation of these financial reports is a form of accountability in public financial management. Audits conducted by the Supreme Audit Agency (BPK) result in audit opinions, which are official statements regarding the reliability of financial reports. In addition, the BPK also provides recommendations for improvements that must be followed up. This study aims to examine the impact of audit findings and follow-up on recommendations on the quality of local government financial reports. The method used is a quantitative approach with ordinal logistic regression analysis, using SPSS Statistics software version 29. The research sample includes districts and cities in West Java Province that received audit opinions from the BPK on their financial statements during the 2019–2023 period, selected using purposive sampling. The data used were secondary data, consisting of summaries of follow-up reports on audit recommendations (TLRHP) and audit reports (LHP) on local government financial reports (LKPD) for the years 2019–2023. The research results indicate that audit findings do not significantly affect the quality of financial reports. However, follow-up on audit recommendations has a positive impact. Overall, both audit findings and follow-up contribute to determining the quality of local government financial reports